My Psalm Has Turned into Weeping Job's Dialogue with the Psalms - Kynes, Will 1981- ([s.l.] Walter De Gruyter GmbH Co.KG, 2012)
Drawing inspiration from the widely recognized parody of Ps 8:5 in Job 7:17-18, this study inquires whether other allusions to the Psalms might likewise contribute to the dialogue between Job, his friends, and God. An intertextual analysis reveals six psalms (1, 8, 39, 73, 107, 139) that serve as subtexts in the Job dialogue. The dialogue thus created between Job and these psalms indicates the concern the book has with the proper response to suffering and the role the interpretation of authoritative texts may play in that reaction. Will Kynes,University of Oxford,UK.
9.2.2. The Friends: Pious Proof-texting
Description based upon print version of record
Teilw. zugl.: Cambridge, Univ., Diss., 2008
Online-Ausg.
In English
Keywords: Suffering -- Biblical teaching; Suffering; Hiob; Intertextualität; Psalmen; Weisheitsliteratur; RELIGION / Biblical Criticism & Interpretation / Old Testament; Job -- Intertextuality -- Wisdom Literature -- Psalms; Intertextuality; Job; Psalms; Wisdom Literature; Electronic books; Hochschulschrift